Efficacy of exogenous phytase supplementation on production performance of commercial broiler (Bangladesh Journal of Animal Science, 2017)
An experiment was conducted to investigate the effect of supplementing of exogenous phytase enzyme on productivity of commercial broilers. Four strains of commercial broiler such as Fast feather, Arbor acres, Cobb-500 and Hubbard classic each having 78 numbers were reared for a period of 5 weeks. A total number of 312 day old broiler chicks were distributed into two dietary treatments i.e. basal diet (Control-T0) and basal diet supplemented with phytase enzyme 1g/kg feed (supplemented-T1). The results indicated that broilers fed on diets supplemented with phytase have gained more body weight when compared with control group (P